(untitled) (Economic and Political Thought, 2018)
The main aim of this article is to present the possibility of internalisation of negative externalities generated by banks with the use of a bank levy introduced in Poland at the beginning of 2016. The conducted survey takes into account Polish banks’ adaptive response to newly implemented tax (tax optimisation) and co-effects of the group response materialised in local interbank and sovereign debt markets. Empirical assessment of the bank levy introduction and evaluation of its externalities internalisation potential is based on statistical data gathered in 2015–2017.